Genetic variation of southeast asian crocodile, Tomistoma schlegelii Muller, using microsatellite and inter simple sequence repeat markers - Astani, Behnam Shafiei (2015)
Tomistoma schlegelii, also referred to as the “false gharial”, is one of the most exclusive and least known of the world’s fresh water crocodilians, limited to Indonesia and Malaysia. The species has been recognized for over a century from a museum specimen, and its distribution has been a mystery for a long time. Its lack of economic value and local cultural significance (the skin is not traded locally) has also contributed to the lack of studies on the false gharial. Tomistoma schlegelii within the Southeast Asia region has been found to suffer from population reduction. This species has to live in small environments, because of the current habitat destruction, hence leading to a steady reduction of species number and, this can be as a reason for an increase in the rate of inbreeding. Nevertheless, lack of information on the genetic variability and structure of the species in Malaysia remains a matter of concern. Hence, the objectives of this study were to determine the current genetic diversity and structure of this endangered species in Malaysia. To achieve this, two types of molecular markers, namely microsatellites (40 primer pairs) and Inter Simple Sequence Repeats (ISSRs, 45 primers) were used. The Department of Wildlife and National Parks (DWNP), Malaysia provided the samples. In this regard, 17 T. schlegelii specimens were collected by the department from different parts of Peninsular Malaysia and Sarawak, and were then transferred to the farms and zoos across the country. The mentioned crocodiles were later subjected to the blood sampling process. Consequently, DNA was isolated from the blood samples of T. schlegelii by using the conventional phenol-chloroform method. The PCR amplification of T. schlegelii DNA was optimized to obtain the most effective annealing temperature and Mg2+ concentration for each individual marker. Out of the 40 microsatellite primer pairs tested 10 were detected as amplifying polymorphic bands, while 36 ISSR primers were detected as producing polymorphic banding patterns from the 45 tested. The observed heterozygosity (HO) and the expected heterozygosity values (HE) of the polymorphic microsatellite loci ranged from 0.588 to 1.000 and 0.470 to 0.891, respectively. The highest average heterozygosity was observed for locus Cj109 with a value of 0.945 and the lowest average heterozygosity was observed for locus Cs15 with value of 0.529. Among the 45 ISSR markers, 36 showed polymorphic banding patterns (80%). The highest number (6) of polymorphic bands was produced by primer UBC811 and the lowest (1 each) by primers PT2, UBC820, UBC834 and UBC868. Interestingly, data from both the microsatellite and ISSR marker systems generated two main clusters. The highest repeat motif similarities to the original species from which the loci were developed for three microsatellite loci, namely Cj16, Amiμ16 and Amiμ15, which originated from C. johnstoni, A. mississippiensis and C. siamensis respectively. The repeat motifs of the Cj16 locus in T. schlegelii were found to be a high match with the repeat motif of the same locus in C. johnstoni, and the difference was only limited to one repeat unit of “CA”. The observed similarity of the repeat motif type of Amiμ16 and Amiμ15 was “AC” and the sizes of the amplified loci in the present study were shorter than the ones reported for the original species. Both microsatellite and ISSR marker systems have high potential for studying the genetic variation of T. schlegelii, and these markers are suitable for conservation genetic programme of this endangered species. Overall, assessment of the results showed that the Malaysian T. schlegelii individuals studied in this research could have originated from a core population of the crocodiles. The lack of opportunity for outbreeding with other populations of crocodiles led to the occurrence of low genetic variation of the species in Malaysia.